Shape-Controlled Synthesis of GaN Nanorods and Their Photoluminescence Property - Mao, Wutao; Bao, Keyan; Zhang, Lianfeng; Wang, Qingfeng; Zhang, Linna (Asian Journal of Chemistry, 2015)
In this paper, an atom-economical and eco-friendly chemical synthetic route was developed to synthesize wurtzite GaN nanorods by the reaction of NaNH2 and the as-synthesized orthorhombic GaOOH nanorods in a stainless steel autoclave at 650 °C. The lengths of the GaN nanorods are in the range of 400-600 nm and the diameters are about 100-300 nm. It is interesting that the initial GaOOH structural motifs were unaffected by the high temperature chemical transformations process. The photoluminescence (PL) of GaN nanorods exhibits emission peak in the blue region, which is possibly attributable to the existence of defect.